Development, Characterization, and In vitro Evaluation of Aceclofenac Emulgel - Sandeep, D. S. (Asian Journal of Pharmaceutics (AJP), 2020)
Aim: The present research work was aimed to develop a novel emulgel for aceclofenac to enhance the drug absorption by the topical application, which overcomes the demerits of oral dosage form and conventional gel system of aceclofenac. Materials and Methods: The emulgels were prepared with carbopol 934 as a gelling agent used in six different concentrations. Span 20 and Tween 20 were included as emulsifying agents in two different concentrations. Liquid paraffin was used as an oil phase, and methyl and propylparaben were included as preservatives. Ethanol was used to dissolve the drug for preparing the aqueous phase and Triethanolamine was added at the end of preparation, as quantity sufficient for pH adjustment. Results: All the formulated emulgels were screened for the parameters, namely, appearance, pH, rheology study, spreadability, swelling index, drug content, and in vitro drug release studies. The optimized formulation AG-4 showed 91.43% of drug release with sustained-release manner up to 6 h, and the particle size analysis reported good size range, and the emulgel was found to be nonirritant and nontoxic which was confirmed by HET CAM test. Conclusion: Aceclofenac can be successfully formulated as emulgel for better-sustained effect and can be a suitable alternative approach to the oral dosage forms for the management of arthritis.